The Effects of Different Kernels in SVM Sentiment Analysis on Mass Social Distancing - Yonatha Wijaya, Komang Dhiyo; Karyawati, Anak Agung Istri Ngurah Eka (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
During this pandemic, social media has become a major need as a means of communication. One of the social medias used is Twitter by using messages referred to as tweets. Indonesia currently undergoing mass social distancing. During this time most people use social media in order to spend their idle time However, sometimes, this result in negative sentiment that used to insult and aimed at an individual or group. To filter that kind of tweets, a sentiment analysis was performed with SVM and 3 different kernel method. Tweets are labelled into 3 classes of positive, neutral, and negative. The experiments are conducted to determine which kernel is better. From the sentiment analysis that has been performed, SVM linear kernel yield the best score Some experiments show that the precision of linear kernel is 57%, recall is 50%, and f-measure is 44%